Emotional management and clinical communication among nursing students: a single institution experience - Yang, Meiqiong; Lin, Pingzhen; Zheng, Limian; Wu, Biyu (Frontiers in Psychiatry, 2024)
Background The development of emotional and clinical communication is crucial for being a nurse. The aim of this study is to evaluate the influencing factors of emotional management and clinical communication competencies among nursing students, to inform strategies for enhancing the management and nursing care practices. Methods This study was a cross-sectional survey. The study period was from December 1 to December 31, 2022, during which nursing students were the population of the survey. The assessments of the emotional management and clinical communication competencies of the nursing students were conducted using the validated Emotion Management Ability Questionnaire and the Clinical Communication Ability Scale, respectively. Results A total of 356 nursing students were investigated in this study. The nursing students had moderate ability of emotional management and clinical communication. The emotional management ability was correlated with the clinical communication ability of nursing students (all p<0.05). The results of multivariate regression analysis indicated that gender, educational level and home place were the independent influencing factors on the emotional management ability in the nursing students (all p<0.05). Family structure, internship time and personality were the independent influencing factors for the clinical communication ability among the nursing students (all p<0.05). Conclusions The competencies in emotional management and clinical communication among clinical nursing students warrant enhancement. It is imperative to implement tailored educational and training programs to optimize the development and performance of nursing students in their clinical training.